A photographic food atlas with portion sizes of commonly consumed foods in Thai Nguyen, Viet Nam - Nguyen, Phuong Hong; Tran, Lan Mai; Hoang, Nga Thu; Trương, Duong Thuy; Tran, Trang Huyen; Huynh, Phuong Nam; Koch, Bastien; McCloskey, Pete; Gangupantulu, Rohit; Braga, Bianca C.; Hughes, David; Gelli, Aulo (International Food Policy Research Institute, 2021)
This Food Atlas provides a photograph series of the 360 meals most commonly eaten by adolescent girls in Thai Nguyen, Viet Nam. It was developed using calibrated portion sizes and standardized methods and consists of pictures, recipes, and portion sizes per meal, including weights. The purpose of this Food Atlas is to improve the accuracy of portion-size estimation during food consumption surveys. The images can be shown to respondents to help them accurately describe the amount of food consumed. The meals were selected using previous food consumption surveys aimed at understanding the eating patterns of urban girls between ages 15 and 17, as well as from traditional cookbooks and national food composition tables. A rapid school survey of 290 teenage girls was also used in Thai Nguyen to refine the final list of 360 meals. When recipes were not available from existing sources for particular meals, the cooking team collected the ingredients and developed recipes based on food composition tables developed by Viet Nam’s National Institute of Nutrition (NIN). Some recipes were also collected from street vendors when other sources did not provide sufficient information. When many recipes were available for a particular meal, the project team prepared and photographed the three most common recipes, prioritizing the preparations used by street vendors. For dishes with varying ingredients, the distribution of ingredient variations from past surveys was tabulated, and the most common ingredient variations were prepared, weighed, and photographed.